Correlation Between Mother’s Nutritional Expertise and Toddler’s Stunting Incidence in Wainyapu Village - Pandi, Mariana; Sari, Ni Luh Putu Dian Yunita; Prihandhani, IGAA Sherlyna; Triana, Komang Yogi (Politeknik Medica Farma Husada Mataram, 2024)
Stunting is one of the world's nutritional challenges, particularly in impoverished and emerging countries. Stunting is an issue since it is connected with a higher risk of morbidity and mortality, as well as inadequate brain development, which leads to delayed motor development and stunted cerebral growth. The mother's health and nutritional status before and throughout pregnancy, the mother's body posture, the close spacing of pregnancies, the mother's adolescence, and poor dietary intake during pregnancy all have an impact on fetal growth and stunting risk. Stunting is influenced by the mother's nutritional expertise. This study aimed to evaluate the correlation between mothers’ nutritional expertise and the toddlers’ stunting incident in Wainyapu Village. This quantitative study employed an analytical survey design and a cross-sectional approach method. The population in this study were mothers who had toddlers 12-59 months and lived in Wainyapu Village. This study employed total sampling technique, with a questionnaire on mothers’ nutritional expertise as the research instrument. The Spearman correlation test was employed during data analysis. The findings yielded that the level of mothers’ nutritional expertise was mostly in the poor category (76.9%), with the incidence of stunting in toddlers as high as (75%), and there was a significant correlation between mothers’ nutritional expertise and the toddlers’ stunting incident as shown by Spearman correlation results were 0.945 with Sig p-value <0.01. It is expected that this study can provide mothers some information to better understand the importance of toddlers’ nutritional expertise in order to avoid stunting